Outer limits the filmgoers' guide to the great science-fiction films - Hughes, Howard 1971- (London I.B. Tauris, 2014)
Howard Hughe's new filmgoers' guide to science-fiction films delves deep into the landmark movies of this ever popular genre, from Metropolis to Avatar and beyond, and covers over 250 more. It explores science-fiction cinema through 26 great films, from the silent classic Metropolis to today.
'Death to the Machines' -- 'Regarded This Earth with Envious Eyes' -- 'Godzilla Is Just a Legend' -- 'I Never Saw Anything Like It!' -- 'You're Next!' -- 'We Are, After All, Not God' -- 'He Has All the Time in the World' -- 'Damn You All to Hell' -- 'My God, It's Full of Stars' -- 'I Love All the Love in You' -- 'The Mysteries Remain' -- 'The Force Will Be with You, Always' -- 'When You Wish upon a Star' -- 'In Space No One Can Hear You Scream' -- 'Nobody Gets Out of Here Alive' -- 'Like Tears in Rain' -- 'It's Weird and Pissed Off' -- 'You Have No Concept of Time' -- 'Hasta La Vista, Baby' -- 'Houston, We Have a Problem' -- 'Now That's What I Call a Close Encounter' -- 'Welcome to the Real World' -- 'By Grabthar's Hammer!' -- 'We See What They See' -- 'Live Long and Prosper' -- 'I See You'.
Includes bibliographical references (pages 289-290) and index.
Keywords: Science fiction films